The Relation Between Bullying and Cyberbullying, Emotional Intelligence, and Empathy in Portuguese Adolescents - Ana Paula Monteiro; Filipa Marques; Inês Carvalho Relva; Margarida Simões; Ana Isabel Sani; Elisete Correia (Adolescents)
Bullying and cyberbullying share in their definition the pattern of aggressive and intentional conduct, characterized by a perceived or observed imbalance and repeated over time. Empathy and emotional intelligence are fundamental individual skills that can enable adolescents to develop less aggressive and more empathetic behaviors. The aim of this study is to explore the frequency of bullying and cyberbullying (victimization and/or aggression), the association of bullying, cyberbullying, empathy, and emotional intelligence, and to explore whether sex, age, educational level, and online recreational time are related to bullying and cyberbullying behaviors. A sample of 599 adolescents, aged between 13 and 21 years old, from basic and secondary schools located in the north of Portugal, participated in the study. The instruments used in the study were the Sociodemographic Questionnaire; the Bullying and Cyberbullying Behavior Questionnaire; the Basic Empathy Scale; and the Self-Perception of Emotional Intelligence Questionnaire. The main results indicated that victims demonstrate greater empathy and emotional intelligence. The results also showed that male adolescents take on more of the role of aggressors in bullying and cyberbullying, while female adolescents take on more of the role of victims. The study underscores the importance of developing and implementing prevention and intervention programs for bullying and cyberbullying, with a focus on promoting empathy and emotional intelligence among adolescents.